ANALISIS PENGARUH WORKPLACE FLEXIBILITY, CONTINUOUS DEVELOPMENT PROGRAM DAN JOB AUTONOMY TERHADAP KINERJA KARYAWAN PERUSAHAAN RINTISAN - Firstianty Wahyuhening Fibriany; Muhammad Zakaria; Flora Grace Putrianti; Riesna Apramilda; Basuki Wisnu; Susatyo Adhi Pramono (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the effect of workplace flexibility, continuous development programs, and job autonomy on employee performance in startups. Improving employee productivity is a key component of the digital sector and growing startups. Therefore, workplace flexibility, continuous development programs, and job autonomy are essential. A quantitative approach was used in this study by surveying 200 startup employees. Multiple linear regression analysis was conducted on the collected data to determine the nature of the relationship between the independent and dependent variables. The results show that workplace flexibility contributes to improving employee performance by creating a better work-life balance. Continuous development programs play a role in improving employee skills and competencies, which contribute to more optimal performance. In addition, job autonomy allows employees to have more control over their work, which has a positive impact on work productivity and efficiency. These findings indicate that to improve employee performance, start-ups need to implement more flexible policies in work scheduling, provide continuous training programs, and provide greater autonomy to employees in carrying out their duties.